Battery, preparation method and power utilization device
Patent Information
- Application Number
- CN202380061446.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-07
- Publication Date
- 2025-04-04
AI Technical Summary
The cycle performance of traditional gel batteries is poor, mainly due to insufficient permeability of the electrolyte inside the electrode plates, resulting in low lithium ion insertion and deintercalation efficiency, which in turn affects the cycle life of the battery.
The swollen electrolyte with pores is introduced into the first active layer of the electrode plate, so that more gel electrolytes are located close to the current collector. Through the multi-layer stacked active sub-layer structure and appropriate swelling electrolyte distribution, lithium ions are increased. The intercalation and deintercalation efficiency is high, and the swelling electrolyte content is controlled in the second active layer to optimize the battery structure.
By improving the intercalation and deintercalation efficiency of lithium ions, the cycle performance of the gel battery is significantly improved, the cycle life of the battery is extended, and the risk of cycle life plummeting due to insufficient electrolyte in the inner layer of the pole piece is reduced.
Smart Images

Figure CN119768928A_ABST
Abstract
Description
Battery, preparation method and power-using device Technical Field
[0001] The present application relates to the field of batteries, and in particular to a battery, a preparation method thereof, and an electrical device. Background Art
[0002] The statements herein merely provide background information related to the present application and do not necessarily constitute prior art.
[0003] As battery energy density continues to increase, battery safety performance also faces greater challenges. Among battery improvements, gel batteries offer better safety performance. However, the cycle performance of traditional gel batteries needs to be further improved.
[0004] Summary of the Invention
[0005] In order to achieve the above-mentioned objectives, the present application provides a battery, including an electrode plate, the electrode plate including a current collector, a first active layer and a second active layer, the first active layer is located on at least one surface of the current collector, and the second active layer is located on the surface of the first active layer away from the current collector, and the first active layer and the second active layer both contain active materials and gel electrolytes; the first active layer also contains a swollen electrolyte having pores, and part of the gel electrolyte in the first active layer is filled in the pores of the swollen electrolyte.
[0006] In the above battery, by introducing the swelling electrolyte, more gel electrolyte can be located in the first active layer close to the current collector, which is beneficial to promote the insertion and / or deinsertion of lithium ions in the electrode sheet and improve the cycle performance of the gel battery.
[0007] In some embodiments, the morphology of the swollen electrolyte is at least one of spherical and spherical-like.
[0008] In some embodiments, the average particle size of the swelling electrolyte is 210 nm to 850 nm.
[0009] In some embodiments, the average particle size of the swelling electrolyte is 300 nm to 500 nm.
[0010] In some embodiments, the weight average molecular weight of the swelling electrolyte is 2,000 to 10,000.
[0011] In some embodiments, the weight average molecular weight of the swelling electrolyte is 3000-8000.
[0012] In some embodiments, the swelling electrolyte includes at least one of a polyacrylate electrolyte, a polyether electrolyte, a polycarbonate electrolyte, a polycarboxylate electrolyte, a silicon-based electrolyte, a polythiol electrolyte, a maleic anhydride electrolyte, and a polysulfate electrolyte.
[0013] In some embodiments, the mass percentage of the swelling electrolyte in the first active layer is 0.01% to 5%.
[0014] In some embodiments, the swelling electrolyte accounts for 1% to 4% by mass of the first active layer.
[0015] In some embodiments, the gel electrolyte has a mesh structure inside the electrode plate.
[0016] In some embodiments, the first active layer includes a plurality of stacked active sublayers, each of the active sublayers contains the active material, the gel electrolyte, and the swelling electrolyte, the swelling electrolyte is uniformly distributed in each of the active sublayers, and the mass percentage of the swelling electrolyte in adjacent active sublayers gradually decreases in a direction away from the current collector.
[0017] In some embodiments, in a direction away from the current collector, the mass percentage of the swollen electrolyte in the adjacent active sublayer decreases by 0.01% to 1%.
[0018] In some embodiments, the mass percentage of the swollen electrolyte in the active sublayer closest to the current collector is 3% to 5%.
[0019] In some embodiments, the mass percentage of the swollen electrolyte in the active sublayer farthest from the current collector is 0.01% to 3%.
[0020] In some embodiments, the thickness of each active sub-layer is 20 μm to 120 μm.
[0021] In some embodiments, the gel electrolyte in each active sublayer is an integrated structure.
[0022] In some embodiments, the mass percentage of the swollen electrolyte in the second active layer is ≤0.5%.
[0023] In some embodiments, the mass percentage of the swollen electrolyte in the second active layer is ≤0.05%.
[0024] In some embodiments, the mass percentage of the swollen electrolyte in the second active layer is 0.
[0025] In some embodiments, the thickness of the second active layer is ≥10 μm.
[0026] In some embodiments, the second active layer has a thickness of 10 μm to 180 μm.
[0027] In some embodiments, the gel electrolyte in the second active layer and the gel electrolyte in the first active layer are in an integrated structure.
[0028] In some embodiments, the thickness of the first active layer is 70 μm to 240 μm.
[0029] In some embodiments, the battery further includes a gel electrolyte layer, which is located on the surface of at least one of the positive electrode sheet, the negative electrode sheet, and the separator of the battery. When the positive electrode sheet and / or the negative electrode sheet has the first active layer and the second active layer, the gel electrolyte layer is at least located on the surface of the second active layer.
[0030] In some embodiments, the thickness of the gel electrolyte layer is 0.5 μm to 4 μm.
[0031] In some embodiments, the electrode plate includes at least one of a positive electrode plate and a negative electrode plate.
[0032] The present application also provides a method for preparing a battery, comprising the following steps:
[0033] forming a first prefabricated active layer on at least one surface of a current collector, the first prefabricated active layer comprising a swelling electrolyte raw material and an active material, and forming a second prefabricated active layer on the first prefabricated active layer, the second prefabricated active layer comprising an active material, to prepare a prefabricated electrode sheet;
[0034] Assembling the battery assembly including the prefabricated electrode sheets into a battery cell;
[0035] injecting a gel electrolyte solution into the battery cell, so that the gel electrolyte solution infiltrates the active material, and the swelling electrolyte raw material absorbs the gel electrolyte solution and swells;
[0036] The gel electrolyte solution is solidified to form a swollen electrolyte having pores, and the pores of the swollen electrolyte are filled with the gel electrolyte.
[0037] In some embodiments, the morphology of the swollen electrolyte raw material is at least one of spherical and spherical-like.
[0038] In some embodiments, the particle size of the swelling electrolyte raw material is smaller than the particle size of the swelling electrolyte.
[0039] In some embodiments, the average particle size of the swelling electrolyte raw material is 200 nm to 800 nm.
[0040] In some embodiments, the average particle size of the swelling electrolyte raw material is 300 nm to 500 nm.
[0041] In some embodiments, the weight average molecular weight of the swelling electrolyte raw material is 2,000 to 10,000.
[0042] In some embodiments, the weight average molecular weight of the swelling electrolyte raw material is 3000-8000.
[0043] In some embodiments, the swelling electrolyte raw material includes at least one of polyacrylate electrolytes, polyether electrolytes, polycarbonate electrolytes, polycarboxylate electrolytes, silicon-based electrolytes, polythiol electrolytes, maleic anhydride electrolytes, and polysulfate electrolytes.
[0044] In some embodiments, forming a first prefabricated active layer on at least one surface of the current collector includes:
[0045] A plurality of prefabricated active sublayers are sequentially formed in a stacked arrangement on at least one surface of the current collector, each of the prefabricated active sublayers comprising the active material and the swelling electrolyte raw material, and the mass percentage of the swelling electrolyte raw material in each of the prefabricated active sublayers gradually decreases in a direction away from the current collector.
[0046] In some embodiments, the reduction range of the mass percentage of the swollen electrolyte raw material in the adjacent prefabricated active sublayers in the direction away from the current collector is controlled to be 0.01% to 1%.
[0047] In some embodiments, the mass percentage of the swollen electrolyte raw material in the prefabricated active sublayer closest to the current collector is controlled to be 3% to 5%.
[0048] In some embodiments, the mass percentage of the swelling electrolyte raw material in the prefabricated active sublayer farthest from the current collector is controlled to be 0.01% to 3%.
[0049] In some embodiments, the thickness of each prefabricated active sub-layer is controlled to be 20 μm to 120 μm.
[0050] In some embodiments, the mass percentage of the swelling electrolyte raw material in the second prefabricated active layer is ≤0.5%.
[0051] In some embodiments, the mass percentage of the swelling electrolyte raw material in the second prefabricated active layer is ≤0.05%.
[0052] In some embodiments, the mass percentage of the swelling electrolyte raw material in the second prefabricated active layer is 0.
[0053] In some embodiments, the gel electrolyte solution includes a polymerizable monomer, an initiator, an electrolyte salt, and a solvent.
[0054] In some embodiments, the curing temperature is 50°C to 70°C.
[0055] In some embodiments, the curing time is 10 hours to 30 hours.
[0056] The present application also provides an electrical device, comprising the battery or the battery prepared by the preparation method. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] To more clearly illustrate the technical solution of this application, the following is a brief introduction to the drawings used in this application. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the drawings without inventive effort.
[0058] FIG1 is a schematic diagram of a secondary battery according to one embodiment of the present application.
[0059] FIG. 2 is an exploded view of the secondary battery according to one embodiment of the present application shown in FIG. 1 .
[0060] FIG3 is a schematic diagram of an electric device using a secondary battery as a power source according to an embodiment of the present application.
[0061] Description of reference numerals:
[0062] 1. Secondary battery; 11. Housing; 12. Electrode assembly; 13. Top cover assembly; 2. Electrical device.
[0063] In order to better describe and illustrate the embodiments and / or examples of the inventions disclosed herein, reference may be made to one or more of the accompanying drawings. The additional details or examples used to describe the accompanying drawings should not be considered to limit the scope of the disclosed inventions, the presently described embodiments and / or examples, and any of the best modes currently understood for these inventions. DETAILED DESCRIPTION
[0064] To facilitate understanding of the present application, a more comprehensive description of the present application will be provided below with reference to the accompanying drawings. The accompanying drawings illustrate preferred embodiments of the present application. However, the present application may be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a more thorough and comprehensive understanding of the disclosure of the present application.
[0065] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this application pertains. The terms used herein in the specification of this application are for the purpose of describing specific embodiments only and are not intended to limit this application. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0066] The "ranges" disclosed herein are defined in terms of lower and upper limits, where a given range is defined by selecting a lower limit and an upper limit, and the selected lower and upper limits define the boundaries of the particular range. Ranges defined in this manner can be inclusive or exclusive of the end values and can be combined arbitrarily, i.e., any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60 to 120 and 80 to 110 are listed for a particular parameter, it is understood that ranges of 60 to 110 and 80 to 120 are also contemplated. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, the following ranges are all contemplated: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4, and 2 to 5. In this application, unless otherwise indicated, the numerical range "a to b" is a shorthand representation of any combination of real numbers between a and b, where a and b are both real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0067] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0068] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0069] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0070] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.
[0071] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true or present, and B is false or absent; A is false or absent, and B is true or present; or both A and B are true, or both A and B are present.
[0072] Unless otherwise indicated, the terms used in this application have the commonly understood meanings generally understood by those skilled in the art. Unless otherwise indicated, the numerical values of the various parameters mentioned in this application can be measured using various measurement methods commonly used in the art. For example, the tests can be performed using the methods described in the examples of this application.
[0073] One embodiment of the present application provides a battery, wherein the positive electrode plate and / or the negative electrode plate includes a current collector, a first active layer, and a second active layer, wherein the first active layer is located on at least one surface of the current collector, and the second active layer is located on a surface of the first active layer away from the current collector, and both the first active layer and the second active layer contain an active material and a gel electrolyte; the first active layer further contains a swollen electrolyte having pores, and a portion of the gel electrolyte in the first active layer fills the pores of the swollen electrolyte.
[0074] In traditional gel batteries, the addition of polymerizable monomers and / or initiators to the electrolyte increases the electrolyte viscosity, making it difficult for the electrolyte to penetrate the interior of the electrode plates, potentially leading to poor cycling performance. In the battery of this embodiment, the introduction of a swelling electrolyte allows more gel electrolyte to be located in the first active layer near the current collector, facilitating the insertion and / or deinsertion of lithium ions within the electrode plates, thereby improving the cycling performance of the gel battery.
[0075] It is understood that a swelling electrolyte refers to an electrolyte that swells in volume after absorbing electrolyte. Introducing a swelling electrolyte into the first active layer can promote the infiltration of the electrolyte into the first active layer during injection, allowing more electrolyte to enter the first active layer. When the electrolyte subsequently solidifies, more gel electrolyte is formed in the first active layer, improving the cycle performance of the battery. At the same time, because the first active layer has more gel electrolyte, it can reduce the risk of the battery's cycle life suddenly decreasing due to insufficient electrolyte in the inner layer of the electrode. In other words, it can reduce the risk of the battery's cycle life suddenly decreasing due to insufficient electrolyte in the inner layer of the electrode.
[0076] It can also be understood that the gel electrolyte has a mesh structure inside the electrode plate, which facilitates the conduction of lithium ions.
[0077] In some embodiments, the morphology of the swollen electrolyte is at least one of spherical and quasi-spherical. Spherical and quasi-spherical swollen electrolytes can form a more regular swollen electrolyte structure, better adapt to the first active layer, and help maintain the stability of the first active layer structure.
[0078] Optionally, the particle size of the swelling electrolyte is 210nm to 850nm. Excessively large particle sizes of the swelling electrolyte are not conducive to grading. At the same time, excessively large particle sizes of the swelling electrolyte may damage the pore structure of the electrode. Excessively small particle sizes of the swelling electrolyte may lead to poor uniformity of dispersion of the swelling electrolyte within the electrode, thereby causing defects within the electrode. For example, when the particle size of the swelling electrolyte is too small, when preparing the electrode slurry, the risk of particle agglomeration may increase, resulting in poor particle dispersion and, in turn, defects in the manufactured electrode. Optionally, the particle size of the swelling electrolyte is 250nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, etc. Optionally, the average particle size of the swelling electrolyte is 300nm to 500nm.
[0079] In some embodiments, the weight average molecular weight of the swelling electrolyte is 2000 to 10000. Generally, the larger the molecular weight of the swelling electrolyte, the larger the corresponding particle size. When the molecular weight of the swelling electrolyte is within this range, the swelling electrolyte can be made to correspond to a suitable particle size, further improving the cycle performance of the battery. For example, the weight average molecular weight of the swelling electrolyte is 2000, 3000, 4000, 5000, 6000, 7000, 8000, 4000, 10000. Optionally, the weight average molecular weight of the swelling electrolyte is 3000 to 8000.
[0080] As a selection example of the swelling electrolyte, the swelling electrolyte includes at least one of polyacrylate electrolytes, polyether electrolytes, polycarbonate electrolytes, polycarboxylate electrolytes, silicon-based electrolytes, polythiol electrolytes, maleic anhydride electrolytes, and polysulfate electrolytes.
[0081] When the first active layer contains a swelling electrolyte, the mass percentage of the swelling electrolyte in the first active layer is 0.01% to 5%. If the mass percentage of the swelling electrolyte in the first active layer is too small, the improvement of the battery cycle performance will be limited. If the mass percentage of the swelling electrolyte in the first active layer is too large, it may reduce the mass percentage of the active material, resulting in a decrease in the energy density of the electrode. Optionally, the mass percentage of the swelling electrolyte in the first active layer is 1% to 4%. Further optionally, the mass percentage of the swelling electrolyte in the first active layer is 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, etc.
[0082] In some embodiments, the first active layer includes multiple stacked active sublayers, each containing an active material, a gel electrolyte, and a swelling electrolyte. The swelling electrolyte is evenly distributed within each active sublayer, and the mass percentage of the swelling electrolyte in adjacent active sublayers gradually decreases as it moves away from the current collector. In the first active layer, the mass percentage of the swelling electrolyte gradually decreases as it moves away from the current collector, forming a first active layer with varying mass percentages of swelling electrolyte. This allows more gel electrolyte to be retained within the first active layer, further improving the battery's cycling performance.
[0083] Optionally, the mass percentage of the swollen electrolyte in adjacent active sublayers decreases by 0.01% to 1% in the direction away from the current collector. This can form a relatively stable transition, making it easier to maintain a relatively stable structure inside the first active layer, further improving the battery's cycle performance. Further optionally, the mass percentage of the swollen electrolyte in adjacent active sublayers decreases by 0.01%, 0.05%, 0.08%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc. Further optionally, the mass percentage of the swollen electrolyte in adjacent active sublayers decreases by 0.1% to 1% in the direction away from the current collector.
[0084] As some examples of the mass percentage of the swollen electrolyte in the active sublayer, the mass percentage of the swollen electrolyte in the active sublayer closest to the current collector is 3% to 5%. For example, the mass percentage of the swollen electrolyte in the active sublayer closest to the current collector is 3%, 3.2%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.8%, 5%, etc.
[0085] As some examples of the mass percentage of the swollen electrolyte in the active sublayer, the mass percentage of the swollen electrolyte in the active sublayer farthest from the current collector is 0.01% to 3%. Alternatively, the mass percentage of the swollen electrolyte in the active sublayer farthest from the current collector is 0.01%, 0.02%, 0.05%, 0.08%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, etc.
[0086] In some embodiments, the thickness of each active sublayer is 20 μm to 120 μm. Alternatively, the thickness of each active sublayer is 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, etc. It is understood that the thickness of each active sublayer can be equal or different.
[0087] In some embodiments, the gel electrolytes in each active sublayer are integrated. In this case, the gel electrolytes in the first active layer are interconnected to form a complete lithium ion transport network, which is conducive to further improving the cycle performance of the battery.
[0088] In some embodiments, the mass percentage of the swollen electrolyte in the second active layer is ≤0.5%. Alternatively, the mass percentage of the swollen electrolyte in the second active layer is ≤0.05%. Further, optionally, the mass percentage of the swollen electrolyte in the second active layer is 0. A lower mass percentage of the swollen electrolyte in the second active layer allows more gel electrolyte to be closer to the current collector, reducing the risk of battery cycling performance degradation due to insufficient electrolyte within the electrode.
[0089] In some embodiments, the thickness of the second active layer is ≥ 10 μm. Optionally, the thickness of the second active layer is 10 μm to 180 μm. Further optionally, the thickness of the second active layer is 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 100 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, etc.
[0090] In some embodiments, the gel electrolyte in the second active layer is integrated with the gel electrolyte in the first active layer. This interconnection between the gel electrolyte in the second active layer and the gel electrolyte in the first active layer facilitates the formation of a complete lithium-ion transport network within the electrode, further improving the battery's cycling performance.
[0091] In some embodiments, the thickness of the first active layer is 70 μm to 240 μm. Alternatively, the thickness of the first active layer is 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, 200 μm, 210 μm, 220 μm, 230 μm, 240 μm, etc.
[0092] In some embodiments, the battery further comprises a gel electrolyte layer, which is located on the surface of at least one of the positive electrode sheet, the negative electrode sheet, and the separator of the battery. When the positive electrode sheet and / or the negative electrode sheet has a first active layer and a second active layer, the gel electrolyte layer is at least located on the surface of the second active layer. When at least one surface of the positive electrode sheet, the negative electrode sheet, and the separator of the battery has a gel electrolyte layer, a more complete lithium ion transmission network can be formed inside the battery, thereby improving the cycle performance of the battery. Optionally, the thickness of the gel electrolyte layer is 0.5μm to 4μm. Further optionally, the thickness of the gel electrolyte layer is 0.5μm, 0.8μm, 1μm, 1.5μm, 2m, 2.5μm, 3μm, 3.5μm, 4μm, etc.
[0093] It is understood that in some embodiments, the electrolyte inside the battery includes a gel electrolyte. It is also understood that inside the battery, the space between the positive electrode sheet, the negative electrode sheet, and the separator is filled with a gel electrolyte.
[0094] It can be understood that the electrode plate includes at least one of a positive electrode plate and a negative electrode plate.
[0095] Another embodiment of the present application provides a method for preparing a battery. The method includes the following steps: forming a first prefabricated active layer on at least one surface of a current collector, the first prefabricated active layer comprising a swelling electrolyte raw material and an active material; forming a second prefabricated active layer on the first prefabricated active layer, the second prefabricated active layer comprising an active material, to prepare a prefabricated electrode plate; assembling the battery assembly including the prefabricated electrode plates into a battery cell; injecting a gel electrolyte solution into the battery cell, allowing the gel electrolyte solution to infiltrate the active material and allowing the swelling electrolyte raw material to absorb the gel electrolyte solution and swell; and solidifying the gel electrolyte solution to form a swelling electrolyte having pores, wherein the pores of the swelling electrolyte are filled with the gel electrolyte.
[0096] In this embodiment, by introducing the swelling electrolyte raw material into the first prefabricated active layer, more gel electrolyte solution can be introduced into the first prefabricated active layer during injection. When the gel electrolyte solution solidifies, the pores of the swelling electrolyte can be filled with gel electrolyte, allowing more gel electrolyte to enter the interior of the electrode. This facilitates the insertion and / or extraction of lithium ions within the electrode, thereby improving the battery's cycling performance.
[0097] It is understood that the first prefabricated active layer may be formed by slurry coating. When forming the first prefabricated active layer, the swelling electrolyte raw material may be mixed into the slurry, and then the slurry may be coated on at least one surface of the current collector to form the first prefabricated active layer.
[0098] In some embodiments, the morphology of the swellable electrolyte raw material is at least one of spherical and quasi-spherical. Spherical and quasi-spherical swellable electrolytes can form a more regular swellable electrolyte structure, better adapt to the first active layer, and help maintain the stability of the first active layer structure.
[0099] It is understandable that the particle size of the swelling electrolyte raw material is smaller than the particle size of the swelling electrolyte. After the swelling electrolyte raw material absorbs the gel electrolyte solution, it swells, thereby increasing its volume, which may cause the particle size of the swelling electrolyte to be larger than the particle size of the swelling electrolyte raw material. Optionally, the particle size of the swelling electrolyte raw material is 200nm to 800nm. For example, the particle size of the swelling electrolyte raw material is 200nm, 250nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, etc. Optionally, the average particle size of the swelling electrolyte raw material is 300nm to 500nm.
[0100] In some embodiments, the weight average molecular weight of the swelling electrolyte raw material is 2000 to 10000. Generally, the larger the molecular weight of the swelling electrolyte raw material, the larger the corresponding particle size. When the molecular weight of the swelling electrolyte raw material is within this range, the swelling electrolyte raw material can be made to correspond to a suitable particle size, further improving the cycle performance of the battery. For example, the weight average molecular weight of the swelling electrolyte raw material is 2000, 3000, 4000, 5000, 6000, 7000, 8000, 4000, and 10000. Optionally, the weight average molecular weight of the swelling electrolyte raw material is 3000 to 8000.
[0101] As some optional examples of the swelling electrolyte raw materials, the swelling electrolyte raw materials include at least one of polyacrylate electrolytes, polyether electrolytes, polycarbonate electrolytes, polycarboxylate electrolytes, silicon-based electrolytes, polythiol electrolytes, maleic anhydride electrolytes and polysulfate electrolytes.
[0102] In some embodiments, forming the first prefabricated active layer on at least one surface of the current collector includes sequentially forming a plurality of stacked prefabricated active sublayers on at least one surface of the current collector, each prefabricated active sublayer comprising an active material and a swelling electrolyte material, with the weight percentage of the swelling electrolyte material in each prefabricated active sublayer gradually decreasing as it moves away from the current collector. This creates a certain concentration difference of the swelling electrolyte material, which facilitates the penetration of the gel electrolyte solution into the inner layer, thereby improving the wetting effect, shortening the wetting time, and increasing energy efficiency.
[0103] It is understood that multiple stacked prefabricated active sublayers can be sequentially formed by slurry coating. When forming each prefabricated active sublayer, the swelling electrolyte raw material can be mixed into the slurry used to form each prefabricated active sublayer according to the corresponding mass percentage, and then the corresponding prefabricated active sublayer can be formed by slurry coating.
[0104] In some embodiments, the mass percentage of the swollen electrolyte raw material in adjacent prefabricated active sublayers is controlled to decrease by 0.01% to 1% in the direction away from the current collector. Alternatively, the mass percentage of the swollen electrolyte raw material in adjacent prefabricated active sublayers is controlled to decrease by 0.01%, 0.05%, 0.08%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc. Further, optionally, the mass percentage of the swollen electrolyte raw material in adjacent prefabricated active sublayers is controlled to decrease by 0.1% to 1% in the direction away from the current collector.
[0105] In some embodiments, the mass percentage of the swelling electrolyte raw material in the prefabricated active sublayer closest to the current collector is controlled to be 3% to 5%. For example, the mass percentage of the swelling electrolyte raw material in the prefabricated active sublayer closest to the current collector is controlled to be 3%, 3.2%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.8%, 5%, etc.
[0106] In some embodiments, the mass percentage of the swelling electrolyte raw material in the prefabricated active sublayer farthest from the current collector is controlled to be 0.01-3%. Alternatively, the mass percentage of the swelling electrolyte raw material in the prefabricated active sublayer farthest from the current collector is controlled to be 0.01%, 0.02%, 0.05%, 0.08%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, etc.
[0107] In some embodiments, the thickness of each prefabricated active sublayer is controlled to be 20 μm to 120 μm. Alternatively, the thickness of each prefabricated active sublayer is controlled to be 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, etc. It is understood that the thickness of each prefabricated active sublayer can be equal or different.
[0108] In some embodiments, the mass percentage of the swelling electrolyte raw material in the second prefabricated active layer is ≤0.5%. Alternatively, the mass percentage of the swelling electrolyte raw material in the second prefabricated active layer is ≤0.05%. Alternatively, the mass percentage of the swelling electrolyte in the second prefabricated active layer is 0. A low mass percentage of the swelling electrolyte raw material in the second prefabricated active layer can provide a buffer space for the gel electrolyte solution to infiltrate the interior of the electrode during injection, promoting the movement of the gel electrolyte solution into the electrode, allowing more gel electrolyte solution to enter the electrode, thereby forming more gel electrolyte inside the electrode, and thus improving the cycle performance of the battery.
[0109] It is understood that the gel electrolyte solution includes a polymerizable monomer, an initiator, an electrolyte salt, and a solvent. Optionally, the polymerizable monomer includes at least one of an ester monomer, an ether monomer, a carbonate monomer, a sulfone monomer, an isocyanate monomer, an amide monomer, a nitrile monomer, a fluorinated monomer, an ether-containing oligomer, and a siloxane monomer. Optionally, the initiator includes at least one of azobisisobutyronitrile, azobisisoheptonitrile, benzoyl, dicumyl peroxide, dibenzoyl peroxide, and ammonium persulfide.
[0110] In some embodiments, the curing temperature is 50° C. to 70° C. Alternatively, the curing temperature is 50° C., 51° C., 52° C., 53° C., 54° C., 55° C., 56° C., 57° C., 58° C., 59° C., 60° C., 61° C., 62° C., 63° C., 64° C., 65° C., 66° C., 67° C., 68° C., 69° C., or 70° C.
[0111] In some embodiments, the curing time is 10 hours to 30 hours. Alternatively, the curing time is 10 hours, 12 hours, 15 hours, 18 hours, 20 hours, 24 hours, 30 hours, etc.
[0112] It is understood that the prefabricated electrode sheet includes at least one of a prefabricated positive electrode sheet and a prefabricated negative electrode sheet. For example, when the current collector is a positive electrode current collector, a prefabricated positive electrode sheet is obtained. When the current collector is a negative electrode current collector, a prefabricated negative electrode sheet is obtained.
[0113] Another embodiment of the present application provides an electrical device, which includes the above-mentioned battery or the battery prepared by the above-mentioned preparation method.
[0114] The secondary battery and the electric device of the present application will be described below with reference to the accompanying drawings as appropriate.
[0115] Typically, a secondary battery consists of a positive electrode, a negative electrode, an electrolyte, and a separator. During the battery's charge and discharge processes, active ions are inserted and removed between the positive and negative electrodes. The electrolyte conducts ions between the positive and negative electrodes. The separator, located between the positive and negative electrodes, primarily prevents short circuits between the positive and negative electrodes while allowing ions to pass through.
[0116] Positive electrode
[0117] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material.
[0118] As an example, the positive electrode current collector has two surfaces facing each other in its thickness direction, and the positive electrode active material layer is provided on either or both of the two facing surfaces of the positive electrode current collector.
[0119] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector may be formed by forming a metal material on a polymer material substrate. Alternatively, the metal material may include but is not limited to one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. Alternatively, the polymer material substrate may include but is not limited to one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).
[0120] As an example, the positive electrode active material may include positive electrode active materials for batteries that are well known in the art. As an example, the positive electrode active material may include at least one of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include but are not limited to at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their modified compounds. Optionally, lithium cobalt oxide includes LiCoO2. Lithium nickel oxide includes LiNiO2. Lithium manganese oxide includes at least one of LiMnO2 and LiMn2O4. Lithium nickel cobalt manganese oxide includes LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM 333 ), LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM 523 ), LiNi 0.5 Co 0.25 Mn 0.25 O2(NCM 211 ), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM 622 ) and LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM 811 ) at least one of. Lithium nickel cobalt aluminum oxide includes LiNi 0.85 Co 0.15 Al 0.05 O2. Examples of olivine-structured lithium-containing phosphates may include, but are not limited to, at least one of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium manganese iron phosphate, and a composite material of lithium manganese iron phosphate and carbon. Optionally, the lithium iron phosphate includes LiFePO4 (LFP). The lithium manganese phosphate includes LiMnPO4. The weight ratio of the positive electrode active material in the positive electrode film layer is 80 to 100 weight percent, based on the total weight of the positive electrode film layer.
[0121] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), a vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, a vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, a tetrafluoroethylene-hexafluoropropylene copolymer, and a fluorine-containing acrylate resin. The weight ratio of the binder in the positive electrode film layer is 0 to 20 weight%, based on the total weight of the positive electrode film layer.
[0122] In some embodiments, the positive electrode film layer may also optionally include a conductive agent. For example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. The weight ratio of the conductive agent in the positive electrode film layer is 0 to 20% by weight, based on the total weight of the positive electrode film layer.
[0123] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent to form a positive electrode slurry. Optionally, the solvent includes N-methylpyrrolidone. The positive electrode slurry has a solid content of 40 to 80% by weight, and the viscosity at room temperature is adjusted to 5000 to 25000 mPa·s. The positive electrode slurry is coated on the surface of the positive electrode collector, dried, and then cold-pressed by a cold rolling mill to form a positive electrode sheet; the positive electrode powder coating unit surface density is 150-350 mg / m 2 The compaction density of the positive electrode is 3.0-3.6g / cm 3 , optional 3.4-3.6g / cm 3 The calculation formula of the compaction density is: compaction density = coating surface density / (thickness of the electrode after extrusion - thickness of the current collector).
[0124] It is understandable that the positive electrode sheet in the embodiment of the present application can be made by using the above-mentioned positive electrode sheet as the positive electrode sheet body and forming a solid electrolyte interface film on the surface of the positive electrode sheet body.
[0125] Negative electrode
[0126] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer provided on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0127] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.
[0128] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base material. The composite current collector may be formed by forming a metal material on a polymer base material. Optionally, the metal material includes at least one of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. The polymer material includes at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).
[0129] In some embodiments, the negative electrode active material may adopt the negative electrode active material for batteries that is well known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxides, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxides, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more. The weight ratio of the negative electrode active material in the negative electrode film layer is 70 to 100 weight %, based on the total weight of the negative electrode film layer.
[0130] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS). The weight ratio of the binder in the negative electrode film layer is 0 to 30% by weight, based on the total weight of the negative electrode film layer.
[0131] In some embodiments, the negative electrode film layer may further include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. The weight ratio of the conductive agent in the negative electrode film layer is 0 to 20% by weight, based on the total weight of the negative electrode film layer.
[0132] In some embodiments, the negative electrode film layer may further include other additives, such as a thickener. The weight ratio of the other additives in the negative electrode film layer is 0 to 15% by weight, based on the total weight of the negative electrode film layer. Optionally, the thickener includes sodium carboxymethylcellulose (CMC-Na).
[0133] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent to form a negative electrode slurry. Optionally, the solvent includes deionized water. The solid content of the negative electrode slurry is 30 to 70% by weight, and the viscosity at room temperature is adjusted to 2000 to 10000 mPa·s; the obtained negative electrode slurry is coated on the negative electrode current collector, and after a drying process, cold pressing, such as rolling, is performed to obtain a negative electrode sheet. The negative electrode powder coating unit area density is 75 to 220 mg / m 2 , the compaction density of the negative electrode is 1.2~2.0g / m 3 .
[0134] It can be understood that the negative electrode sheet in the embodiment of the present application can be made by using the above-mentioned negative electrode sheet as the negative electrode sheet body and forming a solid electrolyte interface film on the surface of the negative electrode sheet body.
[0135] electrolytes
[0136] The electrolyte conducts ions between the positive and negative electrodes. This application does not specify the type of electrolyte, and the electrolyte can be selected based on the needs. For example, the electrolyte can be liquid, gel, or solid.
[0137] In some embodiments, the electrolyte is an electrolyte solution comprising an electrolyte salt and a solvent.
[0138] In some embodiments, the electrolyte salt may be selected from one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium bis(oxalatoborate) (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP), and lithium tetrafluorooxalatophosphate (LiTFOP). The concentration of the electrolyte salt is typically 0.5 to 5 mol / L.
[0139] In some embodiments, the solvent can be selected from one or more of fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS) and diethyl sulfone (ESE).
[0140] In some embodiments, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, and additives that improve battery high or low temperature performance.
[0141] Isolation film
[0142] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical and mechanical stability can be selected.
[0143] In some embodiments, the material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0144] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be formed into an electrode assembly through a winding process or a lamination process.
[0145] In some embodiments, the secondary battery may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.
[0146] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic. Examples of plastics include polypropylene, polybutylene terephthalate, and polybutylene succinate. This application does not particularly limit the shape of the secondary battery, which can be cylindrical, square, or any other shape. For example, Figure 1 shows a secondary battery 1 with a square structure as an example.
[0147] In some embodiments, referring to Figure 2, the outer packaging may include a shell 11 and a top cover assembly 13. The shell 11 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 11 has an opening connected to the receiving cavity, and the top cover assembly 13 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 12 through a winding process or a lamination process. The electrode assembly 12 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 12. The number of electrode assemblies 12 contained in the secondary battery 1 can be one or more, and those skilled in the art can select according to specific actual needs.
[0148] In addition, the present application also provides an electrical device, which includes the secondary battery provided in the present application. The secondary battery can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but is not limited thereto.
[0149] As the electrical device, a secondary battery can be selected according to its usage requirements.
[0150] Figure 3 shows an example of an electric device 2. The electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the electric device's requirements for high power and high energy density of secondary batteries, a battery pack or battery module can be used.
[0151] Another example device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is generally required to be lightweight and thin, and may use a secondary battery as a power source.
[0152] Example
[0153] In order to make the technical problems, technical solutions and beneficial effects solved by this application clearer, the application will be further described in detail below with reference to the embodiments and drawings. Obviously, the described embodiments are only a part of the embodiments of this application, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is in no way intended to limit the present application and its applications. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0154] If no specific techniques or conditions are specified in the examples, the experiments were carried out according to the techniques or conditions described in the literature in the field or according to the product instructions. All reagents or instruments used without specifying the manufacturer are commercially available conventional products.
[0155] Example 1
[0156] (1) Preparation of positive electrode sheets.
[0157] First active layer slurry: polycarbonate diol with a weight average molecular weight of 5000 is mixed into the slurry and stirred evenly to obtain the first active layer slurry. The slurry contains 50% wt of N-methylpyrrolidone solvent, and the mass ratio of the solid component is LiCo 0.1 Ni 0.8 Mn 0.1 O2:PVDF:conductive carbon black=9:0.5:0.5.
[0158] Second active layer slurry: The second active layer slurry contains 50% wt of N-methylpyrrolidone solvent, and the mass ratio of the solid component is LiCo 0.1 Ni 0.8 Mn 0.1 O2:PVDF:conductive carbon black=9:0.5:0.5.
[0159] The first active layer slurry and the second active layer slurry are sequentially coated on the positive electrode current collector and dried to produce a positive electrode sheet. The positive electrode sheet comprises the positive electrode current collector, the first active layer located on the positive electrode current collector, and the second active layer located on the first active layer. The thicknesses of the first and second active layers are 200 μm and 50 μm, respectively.
[0160] (2) Preparation of negative electrode sheets.
[0161] A negative electrode slurry was applied to the negative electrode current collector and dried to produce a negative electrode sheet. The negative electrode slurry contained 50% by weight of N-methylpyrrolidone as a solvent, and the solid components had a mass ratio of graphite: PVDF: conductive carbon black of 8:1:1. The negative electrode sheet consisted of a negative electrode current collector and a negative electrode active layer located on the negative electrode current collector. The thickness of the negative electrode active layer was 150 μm.
[0162] (3) Preparation of gel electrolyte solution.
[0163] Ethylene glycol dicyclopentenyl ether acrylate, polyethylene glycol dimethacrylate, azobisisobutyronitrile, and electrolyte are uniformly mixed in a mass ratio of 2:1:0.3:7. The electrolyte comprises an electrolyte salt and a solvent, wherein the electrolyte salt is 1M LiPF6 and the solvent is a mixture of EC, EMC, and DEC in a volume ratio of 1:1:1.
[0164] (4) Preparation of batteries.
[0165] The positive and negative electrodes, along with the separator, are assembled into a battery cell. A gel electrolyte solution is then injected into the cell. The polycarbonate diol absorbs the solution and swells. After soaking at 25°C for 24 hours, the cell is cured at 60°C for 24 hours. After curing, some of the gel electrolyte fills the pores of the polycarbonate diol.
[0166] Example 2 to Example 21
[0167] Compared with Example 1, the differences between Examples 2 to 21 are that the type of swelling electrolyte and / or the weight-average molecular weight of the swelling electrolyte and / or the mass percentage of the swelling electrolyte in the first active layer and / or the thickness of the first active layer and / or the thickness of the second active layer are different, as shown in Table 1.
[0168] Example 22
[0169] (1) Preparation of positive electrode sheets.
[0170] The positive electrode slurry is coated on the positive electrode current collector and dried to obtain a positive electrode sheet. The positive electrode slurry contains 50% wt of N-methylpyrrolidone solvent, and the mass ratio of the solid component is LiCo 0.1 Ni 0.8 Mn 0.1 O2:PVDF:conductive carbon black = 9:0.5:0.5. The positive electrode sheet includes a positive electrode current collector and a positive electrode active layer located on the positive electrode current collector. The thickness of the positive electrode active layer is 250 μm.
[0171] (2) Preparation of negative electrode sheets.
[0172] First active layer slurry: Polycarbonate diol with a molecular weight of 5000 was mixed into a slurry and stirred uniformly to obtain a first active layer slurry. The slurry contained 50% by weight of N-methylpyrrolidone solvent and the solid components had a mass ratio of graphite: PVDF: conductive carbon black = 8:1:1.
[0173] Second active layer slurry: The second active layer slurry contains 50% wt of N-methylpyrrolidone solvent, and the mass ratio of solid components is graphite:PVDF:conductive carbon black=8:1:1.
[0174] The first active layer slurry and the second active layer slurry are sequentially coated on the negative electrode current collector and dried to produce a negative electrode sheet. The negative electrode sheet comprises the negative electrode current collector, a first active layer located on the negative electrode current collector, and a second active layer located on the first active layer. The thicknesses of the first and second active layers are 200 μm and 50 μm, respectively.
[0175] (3) Preparation of gel electrolyte solution.
[0176] Ethylene glycol dicyclopentenyl ether acrylate, polyethylene glycol dimethacrylate, azobisisobutyronitrile, and electrolyte are uniformly mixed in a mass ratio of 2:1:0.3:7. The electrolyte comprises an electrolyte salt and a solvent, wherein the electrolyte salt is 1M LiPF6 and the solvent is a mixture of EC, EMC, and DEC in a volume ratio of 1:1:1.
[0177] (4) Preparation of batteries.
[0178] The positive electrode sheet, negative electrode sheet and separator are assembled into a battery cell, and the gel electrolyte solution is injected into the battery cell. After soaking at 25°C for 24 hours, it is cured at 60°C for 24 hours.
[0179] The test results of Example 22 are shown in Table 2.
[0180] Example 23
[0181] (1) Preparation of positive electrode sheets.
[0182] First active layer slurry: polycarbonate diol with a molecular weight of 5000 is mixed into the slurry and stirred evenly to obtain the first active layer slurry. The slurry contains 50% wt of N-methylpyrrolidone solvent, and the mass ratio of the solid component is LiCo 0.1 Ni 0.8 Mn 0.1 O2:PVDF:conductive carbon black=9:0.5:0.5.
[0183] Second active layer slurry: The second active layer slurry contains 50% wt of N-methylpyrrolidone solvent, and the mass ratio of the solid component is LiCo 0.1 Ni 0.8 Mn 0.1 O2:PVDF:conductive carbon black=9:0.5:0.5.
[0184] The first active layer slurry and the second active layer slurry are sequentially coated on the positive electrode current collector and dried to produce a positive electrode sheet. The positive electrode sheet comprises the positive electrode current collector, the first active layer located on the positive electrode current collector, and the second active layer located on the first active layer. The thicknesses of the first and second active layers are 200 μm and 50 μm, respectively.
[0185] (2) Preparation of negative electrode sheets.
[0186] First active layer slurry: Polycarbonate diol with a molecular weight of 5000 was mixed into a slurry and stirred uniformly to obtain a first active layer slurry. The slurry contained 50% by weight of N-methylpyrrolidone solvent and the solid components had a mass ratio of graphite: PVDF: conductive carbon black = 8:1:1.
[0187] Second active layer slurry: The second active layer slurry contains 50% wt of N-methylpyrrolidone solvent, and the mass ratio of solid components is graphite:PVDF:conductive carbon black=8:1:1.
[0188] The first active layer slurry and the second active layer slurry are sequentially coated on the negative electrode current collector and dried to obtain a negative electrode sheet. The negative electrode sheet comprises the negative electrode current collector, the first active layer located on the negative electrode current collector, and the second active layer located on the first active layer. The thicknesses of the first and second active layers are 100 μm and 50 μm, respectively.
[0189] (3) Preparation of gel electrolyte solution.
[0190] Ethylene glycol dicyclopentenyl ether acrylate, polyethylene glycol dimethacrylate, azobisisobutyronitrile, and electrolyte are uniformly mixed in a mass ratio of 2:1:0.3:7. The electrolyte comprises an electrolyte salt and a solvent, wherein the electrolyte salt is 1M LiPF6 and the solvent is a mixture of EC, EMC, and DEC in a volume ratio of 1:1:1.
[0191] (4) Preparation of batteries.
[0192] The positive electrode sheet, negative electrode sheet and separator are assembled into a battery cell, and the gel electrolyte solution is injected into the battery cell. After soaking at 25°C for 24 hours, it is cured at 60°C for 24 hours.
[0193] The test results of Example 23 are shown in Table 2.
[0194] Example 24
[0195] Compared with Example 1, the difference of this embodiment is that the preparation of the positive electrode plate is different.
[0196] The preparation method of the positive electrode sheet in this embodiment is as follows:
[0197] First active sub-layer slurry: polycarbonate diol with a molecular weight of 5000 is mixed into the slurry and stirred evenly to obtain the first active layer slurry. The slurry contains 50% wt of N-methylpyrrolidone solvent, and the mass ratio of the solid component is LiCo 0.1 Ni 0.8 Mn 0.1 O2:PVDF:conductive carbon black=9:0.5:0.5.
[0198] Second active sub-layer slurry: polycarbonate diol with a molecular weight of 5000 is mixed into the slurry and stirred evenly to obtain the first active layer slurry. The slurry contains 50% wt of N-methylpyrrolidone solvent, and the mass ratio of the solid component is LiCo 0.1 Ni 0.8 Mn 0.1O2:PVDF:conductive carbon black=9:0.5:0.5.
[0199] Second active layer slurry: The second active layer slurry contains 50% wt of N-methylpyrrolidone solvent, and the mass ratio of the solid component is LiCo 0.1 Ni 0.8 Mn 0.1 O2:PVDF:conductive carbon black=9:0.5:0.5.
[0200] The first active sublayer slurry, the second active sublayer slurry, and the second active layer slurry were sequentially coated on the positive electrode current collector and dried to obtain a positive electrode sheet. The positive electrode sheet comprises a positive electrode current collector, a first active sublayer located on the positive electrode current collector, a second active sublayer located on the first active sublayer, and a second active layer located on the second active sublayer. The thicknesses of the first active sublayer, the second active sublayer, and the second active layer are 100 μm, 100 μm, and 50 μm, respectively. The mass percentages of the swollen electrolyte in the first and second active sublayers are shown in Table 3.
[0201] Example 25
[0202] Compared with Example 1, the difference of this embodiment is that the preparation of the positive electrode plate is different.
[0203] The preparation method of the positive electrode sheet in this embodiment is as follows:
[0204] First active sub-layer slurry: polycarbonate diol with a molecular weight of 5000 is mixed into the slurry and stirred evenly to obtain the first active layer slurry. The slurry contains 50% wt of N-methylpyrrolidone solvent, and the mass ratio of the solid component is LiCo 0.1 Ni 0.8 Mn 0.1 O2:PVDF:conductive carbon black=9:0.5:0.5.
[0205] Second active sub-layer slurry: polycarbonate diol with a molecular weight of 5000 is mixed into the slurry and stirred evenly to obtain the first active layer slurry. The slurry contains 50% wt of N-methylpyrrolidone solvent, and the mass ratio of the solid component is LiCo 0.1 Ni 0.8 Mn 0.1 O2:PVDF:conductive carbon black=9:0.5:0.5.
[0206] The third active sub-layer slurry: polycarbonate diol with a molecular weight of 5000 is mixed into the slurry and stirred evenly to obtain the first active layer slurry. The slurry contains 50% wt of N-methylpyrrolidone solvent, and the mass ratio of the solid component is LiCo 0.1 Ni 0.8 Mn 0.1O2:PVDF:conductive carbon black=9:0.5:0.5.
[0207] Second active layer slurry: The second active layer slurry contains 50% wt of N-methylpyrrolidone solvent, and the mass ratio of the solid component is LiCo 0.1 Ni 0.8 Mn 0.1 O2:PVDF:conductive carbon black=9:0.5:0.5.
[0208] The first active sublayer slurry, the second active sublayer slurry, the third active sublayer slurry, and the second active layer slurry were sequentially coated on the positive electrode current collector and dried to obtain a positive electrode sheet. The positive electrode sheet includes a positive electrode current collector, a first active sublayer located on the positive electrode current collector, a second active sublayer located on the first active sublayer, a third active sublayer located on the second active sublayer, and a second active layer located on the third active sublayer. The thicknesses of the first active sublayer, the second active sublayer, the third active sublayer, and the second active layer are 66.67 μm, 66.67 μm, 66.67 μm, and 50 μm, respectively. The mass percentages of the swollen electrolyte in the first active sublayer, the second active sublayer, and the third active sublayer are shown in Table 3.
[0209] Comparative Example 1
[0210] Compared with Example 1, the difference of this comparative example is that the second active layer slurry is not applied when preparing the positive electrode sheet. The prepared positive electrode sheet includes a positive electrode current collector and a first active layer located on the positive electrode current collector.
[0211] Comparative Example 2
[0212] Compared with Example 1, the difference of this comparative example is that when preparing the positive electrode sheet, the positive electrode slurry does not contain polycarbonate diol, the positive electrode slurry contains 50%wt of N-methylpyrrolidone solvent, and the mass ratio of the solid component is LiCo 0.1 Ni 0.8 Mn 0.1 The positive electrode slurry was coated on the positive electrode current collector and dried to obtain a positive electrode sheet. The active layer of the positive electrode sheet had a thickness of 250 μm.
[0213] Test Case
[0214] The batteries prepared in the examples and comparative examples were subjected to cycling performance testing using the CC-CV method for charging with a constant voltage charge cutoff current of 0.05C and CC discharge with a constant current charge and discharge rate of 0.33C over a voltage range of 2.5 to 4.35V. Battery cycling performance is measured as capacity retention after 100 cycles. The results are shown in Tables 1 and 2, with the unit being %.
[0215] Table 1
[0216] Table 2
[0217] It can be understood that the 2% by mass percentage of the corresponding active layer in Example 22 in Table 2 indicates that in the negative electrode sheet, the swollen electrolyte accounts for 2% by mass of the first negative electrode active layer. The 2% by mass percentage of the corresponding active layer in Example 23 in Table 2 indicates that in the positive electrode sheet, the swollen electrolyte accounts for 2% by mass of the first negative electrode active layer. At the same time, in the negative electrode sheet, the swollen electrolyte also accounts for 2% by mass of the first negative electrode active layer.
[0218] Table 3
[0219] Tables 1 to 3 show that the introduction of a swelling electrolyte into the first active layer improves the cycling performance of gel batteries. Furthermore, when the first active layer is divided into multiple active sublayers and the mass percentage of the swelling electrolyte in adjacent active sublayers decreases as the distance from the current collector increases, the battery's cycling performance improves.
[0220] The technical features of the above-mentioned embodiments can be combined arbitrarily. In order to make the description concise, not all possible combinations of the technical features in the above-mentioned embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0221] The above-described embodiments merely represent several implementation methods of the present application. While the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that a person skilled in the art could make various modifications and improvements without departing from the spirit of the present application, all of which fall within the scope of protection of the present application. Therefore, the scope of protection of the present patent application shall be determined by the appended claims.
Claims
1. A battery comprising an electrode plate, It is characterized in that The electrode plate includes a current collector, a first active layer and a second active layer, the first active layer is located on at least one surface of the current collector, the second active layer is located on the surface of the first active layer away from the current collector, and the first active layer and the second active layer both contain active materials and gel electrolyte; the first active layer also contains a swollen electrolyte with pores, and part of the gel electrolyte in the first active layer is filled in the pores of the swollen electrolyte.
2. The battery according to claim 1, It is characterized in that The swelling electrolyte satisfies at least one of the following characteristics (1) to (2): (1) The morphology of the swollen electrolyte is at least one of spherical and quasi-spherical; (2) The average particle size of the swelling electrolyte is 210 nm to 850 nm; Optionally, the average particle size of the swelling electrolyte is 300 nm to 500 nm.
3. The battery according to any one of claims 1 to 2, It is characterized in that The weight average molecular weight of the swelling electrolyte is 2000 to 10000; Optionally, the weight average molecular weight of the swelling electrolyte is 3000-8000.
4. The battery according to any one of claims 1 to 3, It is characterized in that The swelling electrolyte includes at least one of a polyacrylate electrolyte, a polyether electrolyte, a polycarbonate electrolyte, a polycarboxylate electrolyte, a silicon-based electrolyte, a polythiol electrolyte, a maleic anhydride electrolyte, and a polysulfate electrolyte.
5. The battery according to any one of claims 1 to 4, It is characterized in that The mass percentage of the swelling electrolyte in the first active layer is 0.01% to 5%; Optionally, the mass percentage of the swelling electrolyte in the first active layer is 1% to 4%.
6. The battery according to any one of claims 1 to 5, It is characterized in that The gel electrolyte is in a mesh structure inside the electrode plate.
7. The battery according to any one of claims 1 to 6, It is characterized in that The first active layer includes a plurality of active sublayers arranged in a stacked manner, each of the active sublayers contains the active material, the gel electrolyte and the swelling electrolyte, the swelling electrolyte is uniformly distributed in each of the active sublayers, and the mass percentage of the swelling electrolyte in adjacent active sublayers gradually decreases in a direction away from the current collector.
8. The battery according to claim 7, It is characterized in that The active sublayer satisfies at least one of the following characteristics (1) to (5): (1) In the direction away from the current collector, the mass percentage of the swollen electrolyte in the adjacent active sublayer decreases by 0.01% to 1%; (2) The mass percentage of the swollen electrolyte in the active sublayer closest to the current collector is 3% to 5%; (3) The mass percentage of the swollen electrolyte in the active sublayer farthest from the current collector is 0.01% to 3%; (4) The thickness of each active sublayer is 20 μm to 120 μm; (5) The gel electrolyte in each of the active sublayers is an integrated structure.
9. The battery according to any one of claims 1 to 8, It is characterized in that The second active layer satisfies at least one of the following characteristics (1) to (3): (1) The mass percentage of the swelling electrolyte in the second active layer is ≤0.5%; Optionally, the mass percentage of the swollen electrolyte in the second active layer is ≤0.05%; Optionally, the mass percentage of the swollen electrolyte in the second active layer is 0; (2) The thickness of the second active layer is ≥ 10 μm, Optionally, the thickness of the second active layer is 10 μm to 180 μm; (3) The gel electrolyte in the second active layer is integrally formed with the gel electrolyte in the first active layer.
10. The battery according to claims 1 to 9, It is characterized in that The thickness of the first active layer is 70 μm to 240 μm.
11. The battery according to any one of claims 1 to 10, It is characterized in that It also includes a gel electrolyte layer, which is located on the surface of at least one of the positive electrode sheet, the negative electrode sheet and the separator of the battery. When the positive electrode sheet and / or the negative electrode sheet has the first active layer and the second active layer, the gel electrolyte layer is at least located on the surface of the second active layer; Optionally, the thickness of the gel electrolyte layer is 0.5 μm to 4 μm.
12. The battery according to any one of claims 1 to 11, It is characterized in that The electrode plate includes at least one of a positive electrode plate and a negative electrode plate.
13. A method for preparing a battery, It is characterized in that The steps include: Forming a first prefabricated active layer on at least one surface of a current collector, the first prefabricated active layer comprising a swelling electrolyte raw material and an active material, and forming a second prefabricated active layer on the first prefabricated active layer, the second prefabricated active layer comprising an active material, to prepare a prefabricated electrode sheet; Assembling the battery assembly including the prefabricated electrode plates into a battery cell; Injecting a gel electrolyte solution into the battery cell, so that the gel electrolyte solution infiltrates the active material, and the swelling electrolyte raw material absorbs the gel electrolyte solution and swells; The gel electrolyte solution is solidified to form a swollen electrolyte having pores, and the pores of the swollen electrolyte are filled with the gel electrolyte.
14. The preparation method according to claim 13, It is characterized in that The swelling electrolyte raw material satisfies at least one of the following characteristics (1) to (4): (1) The morphology of the swollen electrolyte raw material is at least one of spherical and quasi-spherical; (2) The particle size of the swelling electrolyte raw material is smaller than the particle size of the swelling electrolyte; Optionally, the average particle size of the swelling electrolyte raw material is 200nm to 800nm; Optionally, the average particle size of the swelling electrolyte raw material is 300nm to 500nm; (3) The weight average molecular weight of the swelling electrolyte raw material is 2000 to 10000; Optionally, the weight average molecular weight of the swelling electrolyte raw material is 3000 to 8000; (4) The swelling electrolyte raw material includes at least one of polyacrylate electrolytes, polyether electrolytes, polycarbonate electrolytes, polycarboxylate electrolytes, silicon-based electrolytes, polythiol electrolytes, maleic anhydride electrolytes and polysulfate electrolytes.
15. The preparation method according to claim 13 or 14, It is characterized in that The forming of a first prefabricated active layer on at least one surface of the current collector comprises: A plurality of prefabricated active sublayers are sequentially formed in a stacked arrangement on at least one surface of the current collector, each of the prefabricated active sublayers comprising the active material and the swelling electrolyte raw material, and the mass percentage of the swelling electrolyte raw material in each of the prefabricated active sublayers gradually decreases in a direction away from the current collector.
16. The preparation method according to claim 15, It is characterized in that The control that the mass percentage of the swollen electrolyte raw material in each of the prefabricated active sublayers gradually decreases in the direction away from the current collector satisfies at least one of the following characteristics (1) to (4): (1) Controlling the reduction range of the mass percentage of the swollen electrolyte raw material in the adjacent prefabricated active sublayer in the direction away from the current collector to be 0.01% to 1%; (2) controlling the mass percentage of the swelling electrolyte raw material in the prefabricated active sublayer closest to the current collector to be 3% to 5%; (3) controlling the mass percentage of the swelling electrolyte raw material in the prefabricated active sublayer farthest from the current collector to be 0.01% to 3%; (4) The thickness of each prefabricated active sublayer is controlled to be 20 μm to 120 μm.
17. The preparation method according to any one of claims 13 to 16, It is characterized in that The mass percentage of the swelling electrolyte raw material in the second prefabricated active layer is ≤0.5%; Optionally, the mass percentage of the swelling electrolyte raw material in the second prefabricated active layer is ≤0.05%; Optionally, the mass percentage of the swelling electrolyte raw material in the second prefabricated active layer is 0.
18. The preparation method according to any one of claims 13 to 16, It is characterized in that The gel electrolyte solution includes a polymerizable monomer, an initiator, an electrolyte salt and a solvent.
19. The preparation method according to any one of claims 13 to 18, It is characterized in that The curing temperature is 50° C. to 70° C.; and / or the curing time is 10 h to 30 h.
20. An electrical device, It is characterized in that A battery comprising the battery according to any one of claims 1 to 12 or a battery prepared by the preparation method according to any one of claims 13 to 19.